Effects of obeticholic acid on lipoprotein metabolism in healthy volunteers. Issue 9 (6th June 2016) - Pencek, R.; Marmon, T.; Roth, J. D.; Liberman, A.; Hooshmand‐Rad, R.; Young, M. A.
Abstract : The bile acid analogue obeticholic acid (OCA) is a selective farnesoid X receptor (FXR) agonist in development for treatment of several chronic liver diseases. FXR activation regulates lipoprotein homeostasis. The effects of OCA on cholesterol and lipoprotein metabolism in healthy individuals were assessed. Two phase I studies were conducted to evaluate the effects of repeated oral doses of 5, 10 or 25 mg OCA on lipid variables after 14 or 20 days of consecutive administration in 68 healthy adults. Changes in HDL and LDL cholesterol levels were examined, in addition to nuclear magnetic resonance analysis of particle sizes and sub‐fraction concentrations. OCA elicited changes in circulating cholesterol and particle size of LDL and HDL. OCA decreased HDL cholesterol and increased LDL cholesterol, independently of dose. HDL particle concentrations declined as a result of a reduction in medium and small HDL. Total LDL particle concentrations increased because of an increase in large LDL particles. Changes in lipoprotein metabolism attributable to OCA in healthy individuals were found to be consistent with previously reported changes in patients receiving OCA with non‐alcoholic fatty liver disease or non‐alcoholic steatohepatitis.